Formulasi dan Stabilitas Fisik Gel Semprot Ekstrak Daun Buas-buas (Premna serratifolia L.) - Weni Puspita; Heny Puspasari; Ayu Shabrina (Universitas Muhammadiyah Surakarta, 2021)
The ethanol extract of buas-buas leaves is known to have high antioxidant activity, so it has the potential to be developed as a pharmaceutical preparation in the form of a spray gel. This study aims to determine the physical stability of EEDB spray gel preparations in various concentrations (1%, 2%, and 3%). Evaluation of physical stability was using the temperature cycling test method with six cycles. Physical stability evaluation of the spray gel preparation includes pH, organoleptic, viscosity, homogeneity, spraying pattern, and adhesive dispersion. Based on the study results, the three EEDB spray gel formula concentrations (1%, 2%, and 3%) showed good physical stability.